PERKUATAN LERENG PADA MENARA SUTT STA 19 +255 JALAN TOL SEMARANG – SOLO SEKSI TINALUN – LEMAH IRENG - Hendra Sugih Arjaya; Elmi Besty Pratiwi; Siti Hardiyati; Indrastono Dwi Atmanto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
The Final Task Slope Reinforcement on SUTT Tower at Sta 19 +255 on Tinalun –Lemah Ireng Section of Semarang – Solo Toll Road describe analysis slope stability in Semarang – Solo toll road project. Development toll road project make slopes at STA 19 +225 beside SUTT tower has a topography with high 61 meter and very step. High rainfall with clay stone layer position feared can make the slope the site vulnerable to landslides.Avalanche simulations to determine the condition of existing safety factor and areas of landslides in two ways: manual (Fellenius) and computer software (PLAXIS V 8.2). Modeling topographic slope in accordance with the existing field conditions soil type was determined by using data stratification boring and the value of existing SPT.Analysis of first treatment planned make terracing with tilt 60º and cutting on peak slopes. Then the slopes gave protection bored piles with a diameter of 0,6 meters. Retrofitting is made on the side of the SUTT tower and at the base of the slopes. The depth of the bored pile on the side of the tower 30 meters from base SUTT tower around SUTT tower like sheet pile. While the depth of bored pile on the base slopes 8 meters listed only in line side toll road. Figures obtained from alternative safe handling is calculated and compared the results with manual (Fellenius) and computer software (PLAXIS V 8.2). The numerical value of safe (safety factor) with PLAXIS before treatment 1,48. After treatment which is calculated of 1.62. Safe rate calculation results obtained from the calculation manual (Fellenius) is not much different from the calculations with computer software (PLAXIS V 8.2). In condition before treatment is 1,36. After given bored pile protection numerical value of safe (safety factor) increase to 1,54. Ratio increasing safety factor before and after treatment around 0,16. For Analysis estimated cost planning total cost need for make protection Slope Reinforcement on SUTT Tower at Sta 19 +255 on Tinalun –Lemah Ireng Section of Semarang – Solo Toll Road Rp 4.037.000.000,00 (Four Bilion Thirty Seven Milion Rupiah).